An emerging approach for the targeting analysis of Dimethoate in Olive Oil: the role of Molecularly Imprinted Polymers based on Photo-Iniferter Induced "Living" Radical Polymerization - Martins, Nuno (2015)
This study concerns the first attempt to prepare molecularly imprinted polymers for the selective recognition of dimethoate using an iniferter polymerization technique (Inif-MIP). The synthesized polymers were fully characterized. SEM micrographs show a large accessibility to the binding sites with a significant improvement in MIP morphology. Inif-MIPs displayed high adsorption capacity (Q = 5.3 mg g 1). The selectivity of this imprinting system was also assessed by means of cross-selectivity assays and the results obtained show that Inif-MIP displays a high selectivity for dimethoate, whereas some structural analogues (omethoate, malathion and methidathion) are poorly retained (6.3–28.7%) or not retained at all (fenthion). Inif-MISPE methodology was implemented by packing Inif-MIPs particles into a Solid Phase Extraction (SPE) cartridge and the loading, washing and eluting steps were optimized. The suitability of this sample preparation technique was demonstrated, as concentrations of dimethoate close to the tolerated maximum residue limits in the olive oil samples could be satisfactorily analyzed with good precision and accuracy. Some remarkable characteristics, like the sorbent reusability (at least 20 cycles without the lost of selectivity), low solvent consumption, reduced sample handling and, moreover higher recovery rates reaching 88% could be ascribed to the Inif-MISPE methodology.